The Role of Mental Health and Educational Programmes in Predicting Quality of Life: A Cross-Sectional Study - Z, Wan Jamaluddin; Supriadi, Nanang; Wijaya, Muhammad Sayid; Suherman, Suherman (Universitas Islam Negeri Raden Intan Lampung, 2022)
The Covid-19 pandemic has significantly impacted adolescents, particularly within the learning environment. Despite the low prevalence of COVID-19 among adolescents and the general mild symptoms or asymptomatic nature of their cases, the pandemic has induced significant psychological changes and social challenges. Therefore, this study focused on quality of life and mental health of students at Indonesian religious colleges during the COVID-19 pandemic, where religious aspects are integral to the curriculum. It adopted a cross-sectional design with an initial analysis using SPSS version 29. The sample included 395 students from various educational programmes, comprising 14% males and 86% females, with an average age of 19.65 years (SD = 1.03). The results showed that mental health was a crucial factor affecting students quality of life, particularly within the Preschool Education programme. Gender disparities were observed in areas such as physical health and depression, necessitating customised support in educational settings. Variations in students' perceived health status were also identified in specific programmes, such as mathematics and guidance education, showing the impact of academic environments. Generally, the study showed the crucial need for targeted interventions to address mental health issues and support students' quality of life during and after the pandemic.